The Effective Method of Solving Unit Commitment Problems Based on The Lagrange Relaxation Technique (The International Journal of Engineering & Information Technology (IJEIT), 2020)
This paper presents the Unit Commitment (UC) and the common constraints that could appear while doing the UC. Also, Dynamic Programming is introduced briefly with its advantages and disadvantages. Lagrange Relaxation (LR) is introduced with its advantages and disadvantage. Finally, a numerical example of the IEEE model with 36 units and 118 buses are used for unit commitment scheduling within 24 hours.